Recent advances in extracellular matrix manipulation for kidney organoid research - Wang, Ren; Sui, Yufei; Liu, Qiuyan; Xiong, Yucui; Li, Shanshan; Guo, Wu; Xu, Yiwei; Zhang, Sheng (Frontiers in Pharmacology, 2024)
The kidney plays a crucial role in maintaining the body's microenvironment homeostasis. However, current treatment options and therapeutic agents for chronic kidney disease (CKD) are limited. Fortunately, the advent of kidney organoids has introduced a novel in vitro model for studying kidney diseases and drug screening.Despite significant efforts has been leveraged to mimic the spatial-temporal dynamics of fetal renal development in various types of kidney organoids, there is still a discrepancy in cell types and maturity compared to native kidney tissue. The extracellular matrix (ECM) plays a crucial role in regulating cellular signaling, which ultimately affects cell fate decision. As a result, ECM can refine the microenvironment of organoids, promoting their efficient differentiation and maturation. This review examines the existing techniques for culturing kidney organoids, evaluates the strengths and weaknesses of various types of kidney organoids, and assesses the advancements and limitations associated with the utilization of the ECM in kidney organoid culture.Additionally, it presents a discussion on constructing specific physiological and pathological microenvironments using decellularized extracellular matrix during certain developmental stages or disease occurrences, aiding the development of kidney organoids and disease models.